Prevalence of Sleep Disorder in Chinese Preschoolers: A National Population-Based Study - Hua J; Lyu J; Du W (Nature and Science of Sleep, 2022)
Jing Hua,1,* Jiajun Lyu,1,* Wenchong Du2 1Shanghai Key Laboratory of Maternal Fetal Medicine, Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, People’s Republic of China; 2NTU Psychology, Nottingham Trent University, Nottingham, UK*These authors contributed equally to this workCorrespondence: Wenchong Du, NTU Psychology, Nottingham Trent University, Burton Street, Nottingham, NG1 4BU, UK, Email vivienne.du@ntu.ac.uk Jing Hua, Shanghai First Maternity and Infant Hospital, Tongji University School of Medicine, 2699 Gaoke Road, Shanghai, People’s Republic of China, Email Jinghua@tongji.edu.cnStudy Objectives: This study provides data on the prevalence of clinical sleep disorders in Chinese preschoolers aged 3– 5 years old and examined their sleep behaviours and problems with a nationally representative sample.Methods: A national population-based cohort study was conducted with 114,311 children aged 3– 5 years old from 551 cities in China. Children’s daily sleep hours and pediatric sleep disorders defined by the Children’s Sleep Habits Questionnaire (CSHQ) were reported by parents.Results: The estimated sleep disorder prevalence was 76.78% (95% CI:76.54%, 77.03%). Rates of specific disorders were as follows: Bedtime resistance (97.00%, 95% CI:96.90%, 97.10%), Daytime sleepiness (77.68%,95% CI:77.43%, 77.92%), Sleep duration (70.24%,95% CI:69.97%, 70.50%), Parasomnia (58.52%,95% CI:58.23%, 58.80%), Sleep anxiety (55.53%,95% CI:55.24%, 55.81%), Sleep onset delay (51.99%,95% CI:51.70%, 52.28%) Night wakings (30.37%,95% CI:30.10%, 30.63%) and Sleep-disordered breathing (21.86%, 95% CI: 21.62%, 22.09%). The prevalence of sleep disorder, daily sleep hours and rates of specific disorder varied across children of different sex and ages.Conclusion: A high prevalence of sleep disorder was found in Chinese preschoolers, and the specific sleep problems of Chinese preschoolers vary from other cultures. A local standard may be required when using the CSHQ to define sleep disorders in children in China. An in-depth investigation into the reasons for the high sleep disorder prevalence should be conducted and supportive intervention should be provided to preschoolers in China.Keywords: sleep disorder, Chinese preschooler, national prevalence, the Children’s Sleep Habits Questionnaire